2020
DOI: 10.1101/2020.08.31.276683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A versatile reporter system to monitor virus infected cells and its application to dengue virus and SARS-CoV-2

Abstract: Positive-strand RNA viruses have been the etiological agents in several major disease outbreaks over the last few decades. Examples of that are flaviviruses, such as dengue virus and Zika virus that cause millions of yearly infections and spread around the globe, and coronaviruses, such as SARS-CoV-2, which is the cause of the current pandemic. The severity of outbreaks caused by these viruses stresses the importance of virology research in determining mechanisms to limit virus spread and to curb disease sever… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…To analyze the dynamics of intermediate filament remodeling in real time, we established a SARS-CoV-2 reporter system (Pahmeier et al, 2020) in which a green fluorescent protein (GFP), tagged with a nuclear localization sequence (NLS), is anchored to the cytosolic side of the ER by the transmembrane domain of Sec61b through a linker containing a recognition sequence for the SARS-CoV-2 main protease 3-chymotrypsin-like (3CL) (Figure 5C, top). Upon infection by SARS-CoV-2, the reporter protein is cleaved by 3CL, releasing the GFP-NLS moiety, which then translocates into the nucleus.…”
Section: Sars-cov-2 Causes Cytoskeleton Remodeling Important For Viramentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the dynamics of intermediate filament remodeling in real time, we established a SARS-CoV-2 reporter system (Pahmeier et al, 2020) in which a green fluorescent protein (GFP), tagged with a nuclear localization sequence (NLS), is anchored to the cytosolic side of the ER by the transmembrane domain of Sec61b through a linker containing a recognition sequence for the SARS-CoV-2 main protease 3-chymotrypsin-like (3CL) (Figure 5C, top). Upon infection by SARS-CoV-2, the reporter protein is cleaved by 3CL, releasing the GFP-NLS moiety, which then translocates into the nucleus.…”
Section: Sars-cov-2 Causes Cytoskeleton Remodeling Important For Viramentioning
confidence: 99%
“…The SARS-CoV-2 reporter construct used for live cell imaging will be described in detail elsewhere (Pahmeier et al, 2020). In brief, it is an engineered fusion protein composed of (from N-to C terminus) green fluorescence protein, the nuclear localization sequence from simian virus 40, a linker sequence containing the consensus cleavage site of the 3CL protease of SARS-CoV-1, and the transmembrane region of Sec61b.…”
Section: Live Cell Imagingmentioning
confidence: 99%
“…To this end, we employed a previously described reporter cell line that utilizes nuclear translocation of a fluorescent protein to identify virus-infected cells ( Fig. 4A ) ( 41 ). Forty-eight hours after reverse transfection of siRNA pools targeting RNAs of the identified interaction partners, cells were infected with SARS-CoV-2 for 24 hours prior to fixation and imaging.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the NS2B/NS3 protease, which is required to process the virus polyprotein at well-defined sites not cleaved by cellular proteases. Previous studies have shown that recombinant proteins engineered to contain suitable cleavage sites can be selectively cleaved by virus-encoded protease, using proteases and corresponding cleavage sites from several viruses including DENV, leading to modest de-repression or translocation of a fluorescent reporter in transfected cells [4][5][6][7][8] .…”
Section: Main Textmentioning
confidence: 99%
“…Various protease-based sensors have been demonstrated in mammalian tissue culture cells [4][5][6][7][8] . These imply that our design could readily be adapted to other important mosquito-borne flaviviruses including dengue virus and yellow fever virus, simply by changing the protease-sensitive linker sequence.…”
Section: Main Textmentioning
confidence: 99%